Torok, Doa Masyarakat Manggarai Tinjauan Teologis dan Problem Inkulturasinya dalam Perayaan Ekaristi - Sudarlin, Filipus (Perspektif, 2014)
Being authentic is one of the main concern of Christians everywhere, including the Catholics in Manggarai, Flores. The faithful Catholics in Manggarai have been trying hard to live out their Catholic faith based on their particular religious experience within their own culture. The article discusses one of the most important element in the Manggaraian religious rite, namely Torok, which can considerably be adopted and incorporated into the holy Eucharist, particularly as prayer of the faithful. In the traditional rite Torok is the poetically composed prayer and, due to its content, it is very essential for the whole rite. It means that without Torok, any kind of customary rites could not be called a rite at all. Highlighting the traditional concept and practice of Torok, the writer develops his theological considerations and then proposes arguments for the local Church on adapting Torok in the Eucharist, the source and summit of the Christian life.